A CIEF‐LIF method for simultaneous analysis of multiple protein kinases and screening of inhibitors. Issue 14 (20th May 2016) - Xiao, Lixia; Liu, Shengquan; Lin, Lihua; Yao, Shouzhuo
Abstract : Here, a CIEF‐LIF method for multiple protein kinase simultaneous analysis and inhibitors throughput screening with fast rate and low cost is presented. Comparing with CZE, CIEF‐LIF exhibited great focusing ability and high separation efficiency for substrate and phosphorylated peptides, and is applicable for multiple kinases simultaneous analysis regardless of their substrate peptides compositions and charge statuses. Thus, highly sensitive analysis for cyclic adenosine 3', 5'‐monophosphate‐dependent protein kinase (PKA) and cyclin‐dependent kinase 1 (CDK1) was achieved in CIEF‐LIF analysis with detection sensitivity up to 1.25 mU/μL and 0.4 mU/μL, respectively, two magnitudes higher than that of CZE and comparable with that in nanomaterials or green fluorescent protein‐based kinase assay. Moreover, the inhibition effect of inhibitors on multiple kinases could be simultaneously readout in a single electrophoretic run, with half maximal inhibitory concentration of H‐89 for PKA and Ro‐3306 for CDK1 calculated as 37.0 and 35.9 nM, respectively, consistent with literatures reported. The CIEF‐LIF also exhibited strong anti‐interference ability in human breast cancer cell lysates analysis and simulators such as forskolin and 3‐isobutyl‐1‐methylxantine assessment. Therefore, CIEF‐LIF is desirable for future biological application and clinical diagnostics and drug discovery.